Lysophosphatidic acid improves oocyte quality during IVM by activating the ERK1/2 pathway in cumulus cells and oocytes. (1st May 2021) - Ma, Yerong; Yang, Weijie; Ren, Peipei; Li, Xiang; Jin, Jiamin; Dai, Yongdong; Pan, Yibin; Jiang, Lingling; Fan, Hengyu; Zhang, Yinli; Zhang, Songying
Abstract: Oocyte IVM technology is an option for fertility preservation in some groups of patients, such as those with polycystic ovary syndrome, patients with ovarian hyperstimulation syndrome, and for patients with cancer. However, the developmental potential of oocytes from IVM still needs to improve. Several previous studies have reported that lysophosphatidic acid (LPA) promotes glucose metabolism, cumulus cell (CC) expansion, and oocyte nuclear maturation. However, the effect of LPA on oocyte cytoplasmic maturation, particularly mitochondrial function, has rarely been studied and the underlying mechanism is largely unknown, which impedes (pre)clinical applications of LPA. In this study, cumulus-oocyte complexes (COCs) and cumulus-denuded germinal vesicle oocytes (DOs) were treated with various concentrations of LPA during IVM, in the presence or absence of the oxidative stressor cyclophosphamide (CTX). In both normal and CTX-damaged COCs, the 25 μM LPA group exhibited improved CC expansion capacity, a higher nuclear maturation rate, and superior mitochondrial function, compared to no LPA treatment. When the concentration of LPA was over 40 μM, detrimental effects of LPA on oocyte maturation occurred. Compared with COCs, the addition of LPA slightly improved oocyte nuclear and cytoplasmic maturation of DOs, but this was not statistically significant. We observed that LPA promotes the activation of extracellular signal-regulated kinase (ERK)1/2, although this was not statistically significant in DOs. Furthermore, LPA could not reverse the negative effect of CC expansion and mitochondrial function after inactivation of ERK1/2 by U0126. RNA-sequencing and RT-PCR results showed that LPA upregulated several ERK1/2 downstream genes related to CC expansion, such as Areg, Cited4, and Ptgs2 . This study demonstrates that LPA improves oocyte quality during IVM through the activation of ERK1/2 pathway CCs and oocytes, which provides evidence for the potential addition of LPA to IVM medium.